Local Wisdom as a Pedagogical Foundation: Developing Information Literacy Materials for 21st Century Skills in South Sumatra - Iwan Sumarlin; Siti Rukiyah; Darwin Effendi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to develop information literacy teaching materials based on South Sumatra’s local wisdom that are valid, practical, and effective in enhancing junior high school students’ 21st century skills specifically critical thinking, creativity, communication, and collaboration. A Research and Development (R&D) approach was employed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects were eighth-grade students at SMP Negeri 1 Tanjung Lubuk. Data were collected through expert validation sheets, teacher and student response questionnaires, observation sheets, and learning outcome tests. Expert validation by material, media, and language specialists confirmed the teaching materials as highly valid. Practicality testing yielded very positive responses from both teachers and students. Effectiveness evaluation, based on improved learning outcomes and 21st century skills assessment, demonstrated effective to highly effective categories. The research innovatively integrates indigenous South Sumatra local wisdom into information literacy instruction, creating culturally responsive pedagogy that simultaneously develops essential 21st century competencies. The validated teaching materials provide educators with ready-to-use, contextually relevant resources for cultivating information literacy while preserving and transmitting regional cultural heritage. This study contributes a replicable development model demonstrating how local wisdom can be systematically embedded within modern competency-based curricula, bridging cultural preservation with future-ready skill development.